Efficacy of purchasing activities and strategic involvement: an international comparison - Yang, Chen-Lung; Lin, Ru-Jen; Krumwiede, Dennis; Stickel, Elizabeth; Sheu, Chwen (My University, 2013)
The purchasing function plays a strategic role in a company’s ability to compete. As globalization continues to increase, what becomes interesting is the effect that national culture may have on purchasing activities and, ultimately, manufacturing competitiveness. This study examines the effects of purchasing activities and the purchasing function’s involvement with corporate strategy on manufacturing competitiveness as it is affected by national differences. In particular, we are interested in the research question: Do purchasing theories built on samples from mainly North American and Western European countries apply in other countries with different cultural contexts? The statistical results provide evidence that the engagement and efficacy of purchasing activities and strategic involvement within companies vary by national culture. Moreover, a particular cultural dimension, Long-term orientation, is significantly related to the efficacy of purchasing activities and strategic involvement. This finding has important implications from the perspective of purchasing decision-making in global operations. Specifically, top managers from different nations could adopt and implement similar purchasing activities, but those activities could lead to different outcomes depending on the culture. The paper concludes by reviewing research limitations and suggests further examination of operations management theories.
Keywords: Global operations management; Purchasing; Supply chain; National difference; GMRG; National culture